Validation of Basic Electronics Modules Integrating Creative Thinking in Passive Component Materials and Its Applications - Hening Ceria (PILLAR OF PHYSICS EDUCATION, 2022)
The purpose of this study is to cultivate students' creative thinking. Students' thinking can have an impact on human development. This was achieved through the results of the Human Development Index survey, which showed that the level of human resource development in Indonesia is still low due to poor student abilities. One of the drivers of increasing students' ability to think creatively is the learning tools used. We need educational tools that can help students improve their thinking skills. One of the most popular learning tools is the critical thinking in it. This research was conducted to develop a basic electronics module that integrates creative thinking in passive component material and its application for physics students, FMIPA, UNP. The type of the study is R and D (research and development). The development in this study uses the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. However, the development of this research only reached the development stage due to the limited time and cost for this research. The data obtained from this study came from the validity test through validity sheet. The worksheet is divided into five sections, which are assessed by our qualified trainers. The average improvement in students' creative thinking is 86.5%. This value states that the development of basic electronics modules integrates creative thinking in passive component materials and the application is declared feasible in terms of product validity tests.